2004
DOI: 10.1007/s00394-004-0504-0
|View full text |Cite
|
Sign up to set email alerts
|

Virgin Olive Oil Study (VOLOS): vasoprotective potential of extra virgin olive oil in mildly dyslipidemic patients

Abstract: EVOO consumption by mildly dyslipidemic patients is associated with favorable changes in circulating markers of cardiovascular condition. Based on current knowledge, these effects may be associated with cardioprotection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
3
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(174 citation statements)
references
References 24 publications
5
153
3
11
Order By: Relevance
“…Data from randomized, controlled intervention studies on the effect of olive oil and its PC consumption on systemic inflammatory markers in humans are scarce. Recently, in two randomized crossover studies, virgin olive oil, rich in polyphenols, was shown to be more effective in lowering LTB 4 and TXB 2 than refined olive oil (ROO), with a low phenolic content, both at postprandial state in healthy subjects (Bogani et al, 2007) and after sustained consumption in mildly dyslipidemic patients (Visioli et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Data from randomized, controlled intervention studies on the effect of olive oil and its PC consumption on systemic inflammatory markers in humans are scarce. Recently, in two randomized crossover studies, virgin olive oil, rich in polyphenols, was shown to be more effective in lowering LTB 4 and TXB 2 than refined olive oil (ROO), with a low phenolic content, both at postprandial state in healthy subjects (Bogani et al, 2007) and after sustained consumption in mildly dyslipidemic patients (Visioli et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The administration of hydroxytyrosol to adult volunteers has been shown to reduce the production of TXB2, an effect that is observable in both hyperlipaemic subjects and patients with type 2 diabetes. In the latter group, a reduction of 46% in serum TXB2 was observed, with a preventive action against thrombotic and microthrombotic events [44,50]. It has also been known for many years that patients with cardiac pathologies, who may have chronic activation of thrombogenic mechanisms (prothrombotic situation) may get benefits from EVOO [28].…”
Section: Thrombotic Profilementioning
confidence: 98%
“…The phenols, on the other hand, in addition to protecting both humans and experimental animal models from the harmful action of free radicals and reducing TXB2, also inhibit platelet aggregation and alteration of the platelet/vascular wall, reduce fibrinogen, factor VII and the principal suppressant of hemostasis (plasminogen activator inhibitor type 1, or PAI-1), thereby increasing fibrinolysis [44][45][46][47][48][49]. The anti-thrombotic role of EVOO phenols in addition to their antioxidant and anti-inflammatory properties are well characterized, was and they has been demonstrated to reduce TXB2 and LTB4 after a meal containing high quantities of EVOO [47].…”
Section: Thrombotic Profilementioning
confidence: 99%
See 2 more Smart Citations